The influence of temperature, seepage and stress on the area and category of wellbore instability - Xiaobo Liu; Jinyou Zhang; Hongge Jia; Tong Zhang; Xuejia Du; Zhongmin Wang (Scientific Reports)
Abstract This study investigates the challenge of borehole instability in shale gas development, focusing on the interactions among temperature, fluid flow, and stress. Using a thermal-hydro-mechanical coupling model of borehole elastic stress combined with a true triaxial rock strength criterion and tensile failure criterion, the research systematically examines the effects of different models on borehole stability in shale formations. The findings reveal that while temperature has a relatively minor impact on the stress distribution and failure zones around boreholes, bottom hole pressure plays a critical role in influencing both the extent of unstable regions and the modes of rock failure. Under varying inclination angles, the unstable zones and failure patterns generally remain consistent, with higher stability observed when drilling aligns with the direction of minimum horizontal stress. Moreover, the study highlights the significance of appropriate drilling fluid density in maintaining borehole stability. Specifically, when the bottom hole pressure ranges from 50.66 to 70.66 MPa, the tensile and shear instability areas are minimized within seven days of contact with the drilling fluid. The research underscores the importance of optimizing drilling fluid density, carefully managing bottom hole pressure, and selecting proper borehole trajectories to enhance stability during shale gas drilling. These findings provide both theoretical insights and practical guidance, contributing to the optimization of shale gas drilling engineering practices.